Acute pancreatitis as the first manifestation of duodenal MALT lymphoma - Ivona Simkova; Karel Urbanek; Vlastimil Prochazka; Michal Konecny; Jan Gregar; Marie Geierova; Vit Prochazka; Eva Buriankova (Biomedical Papers, 2015)
Background: Possibly any tumor that can cause mechanical obstruction of the distal bile duct can induce acute pancreatitis. However, acute pancreatitis as the first clinical manifestation of duodenal lymphoma is extremely rare. Objective: To report the case of a patient with acute pancreatitis as an extremely rare first manifestation of duodenal MALT lymphoma and possible association with erythema nodosum. Methods: Case report of a 66-year-old woman who was diagnosed with acute pancreatitis caused by infiltration with duodenal lymphoma. Results: Acute pancreatitis was confirmed by CT imaging. Detailed investigation revealed a duodenal mass causing pancreatic injury. Histological analysis established the diagnosis of MALT lymphoma. The patient's medical history also included erythema nodosum. Complete remission of the malignancy was achieved with chemotherapy. Conclusion: This is the first published case report of acute pancreatitis caused by the growth of duodenal MALT lymphoma. An association with erythema nodosum is possible.